‘There is No Direct Evidence of Anything’ - Gregory J. Seigworth; Rebecca Coleman (Media Theory)
In this essay, we track back and forth between Lauren Berlant’s and Raymond Williams’ work to assemble a purposefully compact genealogy of mediation that also pays attention to how mediation intersects with and often redraws many taken-for-granted understandings of affect, ideology, aesthetics and materialism. We explore how, for Berlant and Williams, mediation requires a suspension or dislodging of direct cause and effect relations in favour of an intuitive (and conjectural) analytics of the ongoing overdeterminations that circulate through and about any particular affective/historical conjuncture. Reckoning with mediation has a profound impact too on our practices of writing and theorising – as critical-creative impulses, drawn from the intertwining rhythms of experience/experiment, emerge from the changing yet precise situations of the ordinary day-to-day. We argue that such a conceptualisation of mediation offers a productive means for attuning to and transforming the capacities of intellectual work, media/digital culture, and everyday life from within the midst of a continua of transformation.